Crime in the United States 2023 - Hertz Hattis, Shana (Bernan Press, 2023)
Crime in the United States contains findings from the Federal Bureau of Investigation (FBI) of the offenses known to law enforcement. This reference is the most comprehensive official compilation of crime statistics in the United States and is an important addition to your library's collection. While the FBI no longer prints these findings, Bernan Press continues to provide this practical information in convenient book form. In this intricately detailed source, legal and law enforcement professionals, researchers, and those who are just curious will find violent and property crime statistics for the nation as well as for regions, states, counties, cities, towns, and even college and university campuses. Crime in the United States includes statistics for: Offenses known to police Violent crime offenses: murder, forcible rape, robbery, and aggravated assault Property crime offenses: burglary, larcency-theft, motor vehicle theft, and arson Clearance data: crimes solved by police or cleared by exceptional means Persons arrested Police employees: sworn officers and civilian law enforcement personnel Hate crimes with data by offense type, location, bias motivation, victim type, number of victims, and race of offender